Comprehensive review on Fanconi anemia: insights into DNA interstrand cross-links, repair pathways, and associated tumors - Chenyan Fang; Zhoujun Zhu; Jun Cao; Jun Huang; Yipeng Xu (Orphanet Journal of Rare Diseases)
Abstract Fanconi anemia (FA) is a rare genetic disorder caused by defects in the repair of DNA interstrand crosslinks (ICLs)—highly toxic lesions that impede essential processes like DNA replication and transcription, leading to severe genome instability. Clinically, FA presents with a broad spectrum of symptoms, including progressive bone marrow failure, congenital abnormalities, and an elevated predisposition to various malignancies, particularly acute myeloid leukemia and squamous cell carcinomas. This review provides a comprehensive overview of both the endogenous and exogenous sources of ICLs and the DNA repair pathways responsible for their resolution, with a primary focus on the FA pathway. We also discuss the tumorigenic consequences of FA pathway deficiencies, highlighting the molecular mechanisms that contribute to the heightened cancer risk observed in FA patients.